Inflammatory Profile of Different Absorbable Membranes Used for Bone Regeneration: An In Vivo Study - Bizelli, Vinícius Ferreira [UNESP]; Alécio Viotto, Arthur Henrique [UNESP]; Delamura, Izabela Fornazari [UNESP]; Baggio, Ana Maira Pereira [UNESP]; Ramos, Edith Umasi [UNESP]; Faverani, Leonardo Perez [UNESP]; Bassi, Ana Paula Farnezi [UNESP] (MDPI, 2024)
Background: Guided bone regeneration (GBR) has become a necessary practice in implantology. Absorbable membranes have shown advantages over non-absorbable membranes, such as blood support of bone tissue. This study aimed to evaluate five collagen membranes in rat calvaria critical-size defects through a histomorphometric analysis of the inflammatory profile during the initial phase of bone repair. Materials and methods: A total of 72 Albinus Wistar rats were used for the study, divided into six groups, with 12 animals per group, and two experimental periods, 7 and 15 days. The groups were as follows: the CG (clot), BG (Bio-Gide®), JS (Jason®), CS (Collprotect®), GD (GemDerm®), and GDF (GemDerm Flex®). Results: Data showed that the BG group demonstrated an inflammatory profile with an ideal number of inflammatory cells and blood vessels, indicating a statistically significant difference between the JS and CS groups and the BG group in terms of the number of inflammatory cells and a statistically significant difference between the JS and CS groups and the GD group in terms of angiogenesis (p < 0.05). Conclusions: We conclude that different origins and ways of obtaining them, as well as the thickness of the membrane, can interfere with the biological response of the material.
Keywords: angiogenesis; biomaterials; bone regeneration